Azulene‐Based Molecules, Polymers, and Frameworks for Optoelectronic and Energy Applications. Issue 10 (1st September 2020) - Huang, Jiaqian; Huang, Senhe; Zhao, Yazhen; Feng, Boxu; Jiang, Kaiyue; Sun, Sai; Ke, Changchun; Kymakis, Emmanuel; Zhuang, Xiaodong
Abstract: Azulene has a considerably larger dipole moment than its isomer naphthalene; it also has unique physicochemical properties, including different reactivities on five‐ and seven‐membered rings, a dark color, a narrow gap between the highest occupied molecular orbital and lowest unoccupied molecular orbital, and stimulus response. Although azulene  was discovered more than 100 years ago, the use of azulene‐based derivatives can be traced back to five centuries ago. Due to its unusual structure, azulene‐based molecules and materials are widely used in various fields. However, studies on azulene‐based materials have long been hindered by difficulties in the synthesis. Considerably fewer studies have been conducted on azulene‐based derivatives than on naphthalene‐based derivatives. This perspective paper mainly introduces recent reports on the synthesis of azulene‐based aromatic molecules, conjugated polymers, and coordination polymers, in addition to azulene‐based frameworks. The structure–property relationship, optoelectronic applications, and energy‐related applications of azulene‐based derivatives are reviewed, including their use in near‐infrared absorption, organic field‐effect transistors, organic solar cells, and microsupercapacitors. Abstract : Azulene is a parent nonalternant 10π electron nonbenzenoid aromatic hydrocarbon, which makes it an important part of novel materials used in optoelectronics and fields. With the improvement of the preparation methods of azulene‐based derivatives, the types of materials are becoming more abundant, including linear polymers, fused azulenes and nanoribbons, frameworks, etc.